The how and why of producing policy relevant research: perspectives of Australian childhood obesity prevention researchers and policy makers - Robyn Newson; Lucie Rychetnik; Lesley King; Andrew J. Milat; Adrian E. Bauman (BMC, 2021)
Abstract Background Understanding why research is conducted may help address the under-utilisation of research. This study examined the reasons for childhood obesity prevention knowledge production in New South Wales (NSW), Australia, and the factors influencing research choices from the perspective of the researchers and health policy agencies contributing to the research. Methods A literature search of SCOPUS and ISI Web of Knowledge (affiliation and key word searches) was conducted to compile a database of NSW childhood obesity research outputs, published between 2000 and 2015 (n = 543). Descriptive statistics were used to quantify outputs by research type, differentiating measurement, descriptive, and intervention research, systematic reviews and other publications. Interviews were conducted with a sample of researchers drawn from the database (n = 13) and decision makers from health policy agencies who funded and contributed to childhood obesity research in NSW (n = 15). Researcher interviews examined views about societal impacts, why and under what circumstances the research was conducted. Decision-maker interviews examined policy agency research investment and how research was used in decision making. Content analysis and a thematic approach was used to analyse the interview transcripts. Results The research in this case was conducted for mix of reasons including those traditionally associated with academic inquiry, as well as intentions to influence policy and practice. Differences in funding mechanisms, administrative and employment arrangements, and 'who' initiated the research, created differing incentives and perspectives for knowledge production. Factors associated with the characteristics and experience of the individuals involved also influenced goals, as did the type of research conducted. Policy agencies played a role in directing research to address policy needs. Conclusions The findings of this study confirm that researchers are strongly influenced by their working environment. Funding schemes and other incentives to support policy relevant knowledge production are important. Contextual factors such as policy priorities, policy-driven research funding and the embedded nature or strong connections between some researchers and the policy agencies involved, are likely to have influenced the extent to which policy goals were reported in this study.